Impact of Fiscal Policy on Agricultural Output in Nigeria - LAWAL, Adedoyin Isola; FIDELIS, Ernest Onyebuchi; BABAJIDE, Abiola Ayoopo; OBASAJU, Barnabas O.; OYETADE, Oluwatoyese; LAWAL-ADEDOYIN, Bukola; OJEKA, John Dean; OLANIRU, Oluwatosin S. (Journal of Environmental Management and Tourism, 2019)
This study examines the impact of fiscal policy on agricultural output in Nigeria using the most recent official data. The metrics for fiscal policy is government capital expenditure and custom duties on fertilizer. The study used annual time series data obtained from CBN annual statistical bulletin, NCS, and FIRS which was found to be stationary at the order of I(1) and I(0). The order of unit root test led to the use of ARDL estimation method employed in the empirical analysis of this research work. The study found evidence of both short and long run relationship between the variables (VAO, GEX, IDMF, and ACGSF) using both Johansen co-integration and ARDL Bounds test. Although government expenditure (GEX) to agricultural sector was found to be statistically insignificant which recommend that government should increase agriculture capital expenditure to ensure that its contribution is significant. Consequently, custom duties on fertilizer (IDMF) was found to be negatively signed and significant indicating a negative impact on agricultural output. This demands that the policy makers should be prudent in the use of fiscal policy instrument in achieving its desired objective.